Impactos do framework de Basileia na intermediação financeira do setor bancário brasileiro, no período de 2011 a 2020 - Bandeira, Carlos Eduardo (Universidade do Vale do Rio dos Sinos, 2022)
This study seeks to analyze the impact of factors representing prudential regulatory changes in the banking sector on the cost of capital and the price of credit granted. Banks' main activity is financial intermediation, which consists of taking and transforming risks; therefore, prudential regulation was instituted as an insurance against economic crises originating from the financial system, limiting risks’ leverage and establishing a minimum level of capital to be maintained to cover losses: the capital ratio. By limiting banks' ability to expand, prudential regulation has the potential to affect the prices of credit and funding products, or even restrict access to credit. This fact can produce impacts on the economy, restricting investment opportunities. Studies have proposed to analyze these impacts, with disagreements in the conclusions. Thus, this study analyzed the possible impacts resulting from the Basel III regulatory changes in Brazil. Although it did not find evidence of impact on the cost of capital, it identified its relationship with the Selic rate and in the future rates. By the assets side, the study identified that the credit rate has a significant and positive relationship with the capital ratio, the cost of capital and the spread level for each period.
Keywords: Basileia; Bancos; Riscos; Capital; Regulação prudencial; Basel; Banks; Risks; Prudential regulation; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis